Ex-chiral pool synthesis and receptor binding studies of 4-substituted prolinol derivatives - Gmeiner, Peter; Hübner, Harald; et al. (Tetrahedron-Asymmetry, 2003)
Starting from natural 4-hydroxyproline, preparation of the four possible stereoisomers of 4-amino- and 4-aminomethyl-substituted prolinol derivatives, respectively, was accomplished by chemo- and regioselective functional group transformations at the 2- and 4-positions of the pyrrolidine moiety. These building blocks were used as valuable precursors for the preparation of new methoxybenzamide derivatives. Dopamine and serotonin binding studies involving the subtypes D1, D2long, D2short, D3 and D4 as well as 5-HT1A and 5-HT2, respectively, displayed interesting structure activity relationships, especially with respect to the absolute and relative configuration of the test compounds. As a complement to the D3 receptor preferring aminomethylpyrrolidine FAUC 21, the (2R,4R)-aminoprolinol derivative ent-24 (FAUC 65) preferentially recognizing the D4 subtype was developed. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.lphch.exchir